Beauverdia hirtella subsp. glabrata (Amaryllidaceae), a new subspecies from Rio Grande do Sul State, Brazil - Paz Deble, Leonardo (Phytotaxa, 2021)
Beauverdia hirtella comprises two subspecies: hirtella and lorentzii, the former occurs in Uruguay and southern Rio Grande do Sul state, Brazil, while the second subspecies spreads in southeastern Corrientes and eastern Entre Ríos provinces, Argentina. Based on field surveys, study of nomenclatural types and other specimens, and review of literature, the new subspecies Beauverdia hirtella subsp. glabrata is here proposed, being endemic to rocky grasslands in south-central Rio Grande do Sul state, Brazil. The new subspecies differs from the other two subspecies in several aspects, including the glabrous leaves and pedicels, the narrower leaves, and the smaller and nearly spherical or obovate capsules. Beauverdia hirtella subsp. glabrata is here described and illustrated, including comments on distribution, phenology and conservation. The main differences with regards to related taxa and a key to distinguish the taxa of Beauverdia are also provided.